Preventive measures - Sandu, Cristina Emanuela (Eximia, 2023)
The first fundamental human values, namely individual freedom of the person together with freedom of religion, were the main human rights. According to the Romanian Constitution, the fundamental law of the country, the right to liberty is considered to be the most important right of citizens and, at the same time, it is the subject of many conventions, treaties, as well as other acts to which Romania is a party. Individual liberty and security of person may not be violated and shall enjoy special protection in accordance with the principles and norms of international and domestic law. Being part of a social formation, man is obliged to respect the norms that the state institutes. The restriction of man’s freedom must not lead to its annulment, nor must the power of coercion be taken to an exterm, and therefore, in order to remove all suspicion, the intervention of law arises, adapting social relations so as to ensure the balance between coercion and freedom. However, human rights and fundamental freedoms are linked in a well-defined circumstance, which leads to the strengthening of the rule of law. Deviation from the legal order established by the state by citizens leads to the application of a sanction provided for by the law in force. The purpose of this paper is to explore the notions of "procedural measures" and "preventive measures", the classification of procedural measures, as well as preventive ones, the competence of judicial bodies, the role and importance of preventive measures, the general conditions for applying preventive measures, the analysis of preventive measures, as well as their taking, replacement, revocation and legal termination, and last but not least, the remedies by which preventive measures were ordered.